Adobe illustrator CS3 how-tos : 100 essential techniques - Karlins, David (AdobePress ; Pearson Education [distributor], 2007)
Presents one hundred techniques for using Adobe Illustrator CS3, covering such topics as using the Pen tool, using the Eraser tool, viewing layers, creating symbols, defining an interative crop area, and using Live Trace.